THE ROLE OF THE INSPECTORATE ON FINANCIAL GOVERNANCE (SILPA) OF NORTH ACEH DISTRICT GOVERNMENT - Kemala Hayati Vonna; Indra Wijaya; Julia Afrianti (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
The Inspectorate is an internal control unit (SPI) as well as an internal government supervision apparatus (APIP) which carries out management functions in the form of: supervision, control and inspection in government financial governance. The role of regional inspectorates is to ensure that spending or expenses can be accounted for, both in terms of applicable regulations and from the perspective of benefits obtained by the community. Remaining Over Budget Financing (SILPA) is an indicator for assessing compliance with budget use and at the same time as a work manifestation of the inspectorate. On the other hand, the Financial Audit Agency (BPK)'s opinion on government financial governance reports is a barometer of reliability and trust in financial reports, in the context of transparency and accountability in regional financial management. SILPA North Aceh Regency shows that so far it has shown a decline but still tends to fluctuate. On the other hand, the BPK's assessment of government financial governance shows an unqualified opinion (WTP). Referring to the results of this study, the Supervision, Control and Oversight carried out by the Inspectorate of North Aceh Regency has a negative (partial or simultaneous) and significant effect on SILPA of North Aceh Regency. In line with this, it is recommended to the North Aceh Regency Government to allocate a larger budget in order to support the inspectorate's task of realizing budget management within the North Aceh Regency Government.